Postural Stability in Athletes: The Role of Age, Sex, Performance Level, and Athlete Shoe Features - Albina Andreeva; Andrey Melnikov; Dmitry Skvortsov; Kadriya Akhmerova; Alexander Vavaev; Andrey Golov; Viktorya Draugelite; Roman Nikolaev; Serafima Chechelnickaia; Daria Zhuk; Alexandra Bayerbakh; Vladislav Nikulin; et al. (MDPI AG, 2020)
The effects of different factors-such as age, sex, performance level, and athletic shoe features-on postural balance in athletes remain unclear. The main objective of our study is to identify the features of postural stability in athletes of different age, sex, performance level, and using different types of athletic shoes. This study assessed postural stability in athletes (n = 936, 6-47 years) in a normal bipedal stance with eyes open (EO) and eyes closed (EC). Postural stability was evaluated based on the center of pressure (COP), sway area (AS), and velocity (VCP) while standing on a stabiloplatform. Children (6-12 years) and teen athletes (13-17 years) showed reduced AS-EO (p < 0.01) and VCP-EO (p < 0.01) compared to control (n = 225, 7-30 years). In male and female athletes aged 18+, only VCP-EC was lower versus control. In females (13-17 and 18+), VCP-EO and EC were lower than in males (p < 0.05). Only in the Shooting group, the athletes' performance levels had an effect on VCP-EO (p = 0.020). Long use of rigid athletic shoes with stiff ankle support was associated with reduced posture stability. Postural stability in athletes was mostly influenced by the athlete's age, and, to a lesser extent, by their sex, performance level, and athlete shoe features.